2017
DOI: 10.1080/19336950.2016.1249076
|View full text |Cite
|
Sign up to set email alerts
|

TRPV3 mutants causing Olmsted Syndrome induce impaired cell adhesion and nonfunctional lysosomes

Abstract: TRPV3 is a non-selective cationic channel and is important for several physiological functions. It can be activated by physiological temperature and selective endogenous and exogenous compounds. TRPV3 is one of the key ion channel involved in Ca 2C -signaling in keratinocyte and thus involved in skin-related functions. Recently, naturally occurring mutations in TRPV3, namely G573A, G573S, G573C and W692G have been detected which are linked with the development of pathophysiological conditions such as Olmsted S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…Recently, some mutations in TRPV3: G573A, G573S, G573C and W692G have been detected leading to such disorders like Olmsted Syndrome (OS) [33,34] as well as other skin disorders [35]. These mutants were mainly retained in the ER [36] leading to reduced surface localization.…”
Section: Trpv3 Channel In Ermentioning
confidence: 99%
“…Recently, some mutations in TRPV3: G573A, G573S, G573C and W692G have been detected leading to such disorders like Olmsted Syndrome (OS) [33,34] as well as other skin disorders [35]. These mutants were mainly retained in the ER [36] leading to reduced surface localization.…”
Section: Trpv3 Channel In Ermentioning
confidence: 99%
“…While being predicted to be an intracellular transmembrane protein by SURFY (score: 0.2954), SURFY2 predicted TRPV3 to be a surface-exposed transmembrane protein (score: 0.8383). Even though experimental subcellular localization data is still sparse for TRPV3, GFP-tagged TRPV3 expressed in a keratinocyte cell line has been shown to localize at the plasma membrane (29), substantially bolstering the prediction claim made by SURFY2. Here, the discrepant predictions could be explained by the absence of N-X-S/T glycosylation sites, the most relevant feature in SURFY, as well as the low non-cytoplasmic cysteine counts and absence of non-cytoplasmic C-glycosylation already encountered in the case of KCNT1.…”
Section: Investigating the Most Confident Re-classifications Of Transmentioning
confidence: 89%
“…Though initially it was assumed that all TRP channels are primarily localized in the plasma membrane, later reports have confirmed that different TRP channels have different yet specific distributions to subcellular membrane systems, including ER, Lysosome or endosome, where they participate complex tasks such as regulation of membrane trafficking signal transduction, maintenance of ion and pH homeostasis (Dong et al 2010;Yadav & Goswami. 2016).…”
Section: Presence Of Trp Channels In Mitochondriamentioning
confidence: 99%